Jaroslav Goll's school in the Czech historiography (late 19th – early 20th centuries) - T.V. Gimadeev (Ученые записки Казанского университета: Серия Гуманитарные науки)
Jaroslav Goll’s school, a noticeable phenomenon of the Czech historiography, was discussed. This school arose from J. Goll’s historical seminar at the Czech Faculty of Philosophy in Prague in the late 19th century. J. Goll’s students, the first generation of Czech professional historians, defined the Czech historical science development during the subsequent 50 years. The phenomenon of J. Goll’s school was for the first time analyzed based on the approaches of the contemporary Russian historiography. The anthropological and social aspects of J. Goll’s school were considered. Some facts of J. Goll’s biography were also mentioned. It was concluded that J. Goll’s school was a strong and leading scientific and pedagogical school. It had the basic elements of a scientific school as a social group. A great variety of research themes and methodological approaches within the school was determined by the wide range of problems covered by its research program. The revision of F. Palacký’s concept of Czech history initiated by J. Goll required multilateralism within the school. J. Goll did his best to preserve the school unity up to the World War I.